2020
DOI: 10.1177/0954406220957706
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable adhesives and adhesion processes for the footwear industry

Abstract: The key to sustainable development in the footwear industry through the principles of circular economy lies in taking care of the design, as well as the introduction of innovative and more resource efficient materials and processes to reduce or avoid the use of water, energy, hazardous chemicals and to minimise emissions and waste. In fact, the environmental footprint is already being considered as another requirement of the footwear through eco-design. In this sense, previous studies carried out by INESCOP re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It should be noted that all cases in which oxygen plasma treatments have been applied improve the adhesion of the bonds studied and exceed the minimum quality requirements demanded for footwear according to standard tests (EN 15307:2015;Arán-Aís et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that all cases in which oxygen plasma treatments have been applied improve the adhesion of the bonds studied and exceed the minimum quality requirements demanded for footwear according to standard tests (EN 15307:2015;Arán-Aís et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Plasma treatment increases the surface energy values, whose dispersive component is decreased and polar component is increased in all the treatments. The chemical modification produced on the materials surface is translated into an increase in the polarity, wettability and compatibility of the substrates with the adhesive, particularly in the treatments in which the both components, nonpolar and dispersive ara balanced, such as 30 s -100% and 300 s -50% for TPU and EVA, due to the need for a balance of polarity on the surface (Yáñez-Pacios and Martín-Martínez, 2018;Ngoc and Thai, 2017;Arán-Aís et al, 2020). TPU or EVA joints.…”
Section: Resultsmentioning
confidence: 99%
“…Sustainability is a crucial factor for the viability of the European footwear industry. The footwear and related industries are immersed in a process of transformation towards a circular economy, in which a greater use of raw materials is introduced, as well as the implementation of more efficient processes in terms of energy consumption with less environmental impact, so that they contribute to a lesser generation of waste, as well as its reuse and/or valuation [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, few authors have studied the plasma polymerisation process of different organosilicon compounds, such as HMDSO on leather and synthetic materials [ 30 ], for the development of hydrophobic coatings [ 31 , 32 , 33 , 34 ]. Previous work by the authors showed preliminary evidence of the use and optimisation of plasma technology [ 35 , 36 , 37 ] with enhanced hydrophobicity at high water contact angles in leather for footwear applications [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%